Antithymocyte Globulin Facilitates Alloreactive T-cell Apoptosis by Means of Caspase-3: Potential Implications for Monitoring Rejection-Free Outcomes. Issue 1 (January 2015) - Ashokkumar, Chethan; Sun, Qing; Ningappa, Mylarappa; Higgs, Brandon W.; Mazariegos, George; Zeevi, Adriana; Sindhi, Rakesh
Abstract : Background: Alloreactive T-cell apoptosis may explain reduced immunosuppression requirements with proapoptotic immunosuppression and among rejection-free recipients. This possibility remains unproven. Methods: Apoptotic (caspase-3+, cathepsin B+) and inflammatory (CD154+) T-cell subsets were evaluated before and after adding rabbit antithymocyte globulin (rATG) to mixed lymphocyte co-cultures between human leukocyte antigen-mismatched peripheral blood lymphocytes from healthy adults. In random samples from children with liver (LTx-20) and intestine (ITx-13) transplantation, apoptotic T cells were evaluated for association with rejection-free outcomes using the caspase-3 substrate, phiphilux. Results: In mixed lymphocyte co-cultures between normal human peripheral blood lymphocytes, (1) frequencies of memory (M) and naive (N) Th and Tc, which expressed activated caspase-3, were enhanced most by the combination of allostimulation and rATG, than either stimulus alone. These findings were confirmed with antibody to activated caspase-3, phiphilux, and terminal deoxynucleotide transferase-mediated dUTP nick-end labeling (TUNEL) assay; (2) frequencies of Th subsets, which expressed activated cathepsin B, were similarly increased with combined stimulation. Tc seemed resistant to cathepsin B activation; (3) with increasing rATG concentrations, proportionately more allospecific CD154+T-cytotoxic memory cells (TcM) survived than TcM, resulting in relative enrichment of allospecific CD154+TcM. In random blood samples, phiphilux+T-cell subset frequencies were higher among 14 rejection-free LTx and ITx recipients and demonstrated a greater increase with ex vivo rATG pretreatment than 19 rejectors. In logistic regression analysis, phiphilux+TcM associated best with rejection-free outcomes with a sensitivity of 57% and a specificity of 89%. Conclusion: Rabbit antithymocyte globulin facilitates apoptosis of alloreactive T cells by means of caspase-3 activation, which may explain its steroid-sparing effect in pediatric liver and intestine recipients. Apoptotic susceptibility of T-cytotoxic memory cells, which resist cathepsin B activation, may distinguish rejection-free and rejection-prone liver recipients. Abstract : Rabbit anti-thymocyte globulin increases apoptosis among both helper and cytotoxic human T cell subsets in vitro during allogeneic stimulation. Apoptotic cells increase in peripheral blood in rejection-free pediatric liver transplant recipients. Supplemental digital content is available in the text.